Tecnología de información y comunicación y su influencia en el proceso de enseñanza aprendizaje en el área de matemática a los estudiantes del bachillerato de la Unidad Educativa “23 de Junio” del Cantón Baba, Provincia Los Ríos - Olaya Arzube, Ixzoda Esmeraldas (2017)
It was carried out this research project was to confirm the little importance that information technology and communication in the teaching-learning process of the area of mathematics in high school students being a fundamental basis in the development of the Knowledge and skills. This situation is generated in which the students of the High School of the Educational Unit June 23 Baba has a drawback of learning mathematics so we expose the following proposal: Develop a manual on the use of information technology and communication for Mathematics teaching The main objective is to determine the influence of Information and Communication Technology in the teaching process in the area of mathematics to the students of the Baccalaureate of the Educational Unit "23 de Junio" of the canton Baba, Los Ríos province.